2006
DOI: 10.1159/000093236
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Patent Foramen Ovale: A Residual Coincidence or a Pathophysiological Intrigue?

Abstract: Migraine is one of the most common neurological disorders and one of the most frequent primary headaches. It imposes a significant burden on the affected individuals, society and health care system. As the etiology and pathophysiology of migraine are not well understood, treatment is largely symptomatic. Patent foramen ovale is a remnant of a fetal circulation and is highly prevalent in the general population. Its presence was linked to several disorders including migraine. The aim of this review was to search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 216 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…A connection between migraine (especially migraine with aura), stroke, and PFO has been established [5863]. Studies have shown that the prevalence of PFO in patients with migraine is about 2.5 times greater in comparison with patients who do not suffer from migraine [64, 65].…”
Section: Clinical Condition In Which Mes May Be Detectedmentioning
confidence: 99%
“…A connection between migraine (especially migraine with aura), stroke, and PFO has been established [5863]. Studies have shown that the prevalence of PFO in patients with migraine is about 2.5 times greater in comparison with patients who do not suffer from migraine [64, 65].…”
Section: Clinical Condition In Which Mes May Be Detectedmentioning
confidence: 99%
“…The presence of PFO was also studied in hypobaric decompression sickness in altitude flyers and astronauts [25], high-altitude pulmonary edema [26], platypnea-orthodeoxia syndrome [27], brain abscess [28], transient global amnesia [29], spinal cord ischemia [30], and systemic embolization in solid organs as well as in upper and lower extremities and in migraine [31,32,33,34,35]. All of these studies are at best case series reports, and no cause-effect relationship can be established based on them.…”
Section: Pfo and Coexisting Conditionsmentioning
confidence: 99%
“…In cases of persistent RLS or during Valsalva maneuver, part of these vasoactive substances could bypass pulmonary filter, thus causing ‘metabolic RLS’, and directly enter the arterial circulation activating platelets, or exerting their action on cerebral vasculature. This hypothesis was also discussed in the pathogenesis of migraine [50]. There was one study that demonstrated a correlation between the degree of RLS and the arterial levels of norepinephrine and serotonin [51].…”
Section: Paradoxical Embolism and Rlsmentioning
confidence: 99%
“…Most v-aCS are through a patent foramen ovale (PFO) which can be found on post-mortem in around 27% of the population [3]. V-aCS may also be associated with migraine [4, 5], retinal artery occlusion [6] and decompression sickness in divers [7]. Transcranial Doppler ultrasound (TCD) provides a simple, reproducible [8] non-invasive test for v-aCS with sensitivity 68–100% and specificity 70–100% for PFO detection when compared with transoesophageal echocardiography (TOE) [9, 10].…”
Section: Introductionmentioning
confidence: 99%